Ananalysis Of Ismubaristik Curriculum Management Towards Students Character Building - Ivana Goa; Abd. Rahman; Nuraini Nuraini (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
The Ismubaristic curriculum was formed or designed by Iwan Kurniawan as the principal of SD Muhammadiyah 7 Bandung. Understanding the ismubaristic curriculum is a combination of 6 subjects, consisting of Islamic learning which contains 2 (two) subjects, namely Al-Islam Qur'an and Al-Islam Hadith, Muhammadiyah, Arabic, English, while ICT is combined with Muhammadiyah. . This curriculum was formed because it started with the principal's anxiety about the declining morals and ethics of students who were influenced by the times. Based on the problems above, the objectives of this research are as follows: (1) planning of the ismubaristic curriculum in the formation of student character in SD Muhammadiyah 7 Bandung which is carried out by the principal. (2) the implementation of the ismubaristic curriculum in the formation of student character at SD Muhammadiyah 7 Bandung. (3) the evaluation used to determine the success of the implementation of the ismubaristic curriculum in the formation of student character at SD Muhammadiyah 7 Bandung. This study uses a qualitative approach that is naturalistic in nature, the data is described in a natural state or as it is and the data collected is in the form of words or pictures rather than numbers. The results of this study are: (1) planning in the ismubaristic curriculum, namely: forming a curriculum development team, then setting the curriculum foundation, determining goals, formulating curriculum content which contains 5 (five) subjects namely English, Arabic, Al-Islam Qur'an. an, Al-Islam Hadith, Kemuhammadiyahan and ICT, make semester programs, monthly programs, weekly programs, namely the Weekly Lesson Plan Ismubaristik, daily programs namely Daily Subject, Daily Activities. Next, determine the curriculum method, determine the allocation of study time, determine learning resources, and prepare curriculum evaluations. (2) the implementation carried out in the ismubaristic curriculum, namely: implementing the ismubaristic curriculum learning in accordance with the planning stages that have been prepared previously at the Ismubaristic curriculum planning stage, namely by using learning strategies and methods, learning resources, learning time and place, learning assessment. (3) the evaluation carried out in the ismubaristic curriculum, namely: it has led to the goals that have been previously set, the evaluation strategy is carried out with munaqosah, namely by direct question and answer with students both from memorization, Koran reading techniques, foreign languages. In addition, there are Grade Advancement Skills Requirements (SK3) and graduate skills requirements which serve as benchmarks and also become an ismubaristic curriculum evaluation strategy. Furthermore, the evaluation model uses a quantitative evaluation model, which is to assess the level of change from the beginning of learning until after doing a test or evaluation.